A Study on Occupational Health Hazards of Sanitary Workers in Greater Chennai City Corporation - S. Ajith, V. Rajendran (Mathematical Statistician and Engineering Applications, 2022)
An estimated 1.2 million scavengersare work in the country to keep our environment safe. These sanitary workers’ working conditions have remained virtually unchanged for over a century. Apart from the social atrocities that these workers face, their occupation exposes them to certain health risks. Exposure to dangerous gases such as methane and hydrogen sulphide, cardiovascular degeneration, musculoskeletal disorders such as osteoarthritis and intervertebral disc herniation, infections such as hepatitis, leptospirosis, and helicobacter, skin problems, respiratory system problems, and altered pulmonary function parameters are among the health risks. This paper made an attempt to identify the occupational health hazards on sewage workers in Chennai Corporation.